The 1.8 Å resolution structure of hydroxycinnamoyl-coenzyme a hydratase-lyase (HCHL) from Pseudomonas fluorescens, an enzyme that catalyses the transformation of feruloyl-coenzyme A to vanillin - Leonard, P.M (2020)
10.1107/S0907444906039199